Assessoria de comunicação para APAE de Tapejara - RS - Kemmerich, Dorli Jamir (2018)
His work sought to advise, based on the knowledge acquired in the journalism course, the entity APAE de Tapejara, performing a work of advice in communication. In the universe of existing forms of communication, the FACEBOOK social network was the platform used for the development of the aforementioned Course Completion Work. In the period that comprised the months of April to June 2018, actions aimed at personalizing the page maintained by the APAE entity in Facebook were developed by the academics. Thank you cards for donations received; video testimonials of people who value the work of APAE; creation of events promoted by the entity, among other activities, guided this advice in communication. The work sought, in the dialogue with members of the management, to identify what would be the main changes that were necessary in the reelaboration of the page; and defended the personalization of the posts, giving periodicity to the published content and standardization of the institutional image. At the end of this study, the scope of the publications and the increase of the visibility achieved by the work developed were evaluated. In addition to supporting the institution in the elaboration and distribution of content, the students sought to emphasize, for the direction of the organization, the importance of a permanent internship in the area of ​​social communication.